The financial structure of Singapore - Monetary Authority of Singapore ([Singapore] : Economics Dept., Monetary Authority of Singapore, 1977)
The publication contains a brief description of the financial institutions and markets, their structure, functions and recent development. A description of the exchange control system and the manner in which monetary and banking policies are formulated have also been included
osc 31/01/2019
Loans
Keywords: Finance; Singapore